From cassava to gari: mapping of quality characteristics and end-user preferences in Cameroon and Nigeria - Ndjouenkeu, R.; Kegah, F.N.; Teeken, Béla; Okoye, B.C.; Madu, Tessy; Olaosebikan, O.; Chijioke, Alamu Ugo; Bello, A.A.; Osunbade, A.O.; Owoade, D.; Takam-Tchuente, N.H.; Njeufa, E.B.; et al. (Wiley, 2021)
User’s preferences of cassava and cassava products along the value chain are supported by specific root quality characteristics that can be linked to root traits. Therefore, providing an evidence base of user preferred characteristics along the value chain can help in the functional choice of cassava varieties. In this respect, the present paper presents the results from focus group discussions and individual interviews on user preferred quality characteristics of raw cassava roots and the derived product, gari, – one of the major cassava products in Sub‐Saharan Africa – in major production and consumption areas of Cameroon and Nigeria. Choice of cassava varieties for farming is mainly determined by the multiple end uses of the roots, their agricultural yield and the processing determinants of roots that support their major high‐quality characteristics: size, density, low water content, maturity, colour and safety. Processing of cassava roots into gari goes through different technological variants leading to a gari whose high‐quality characteristics are dryness, colour, shiny/attractive appearance, uniform granules and taste. Eba, the major consumption form of gari in Cameroon and Nigeria, is mainly characterised by its textural properties: smoothness, firmness, stickiness, elasticity and mouldability. Recommendations are made, suggesting that breeding will have to start evaluating cassava clones for brightness/shininess, as well as textural properties such as mouldability and elasticity of cassava food products, for the purpose of supporting decision‐making by breeders and the development of high‐throughput selection methods of cassava varieties. Women are identified as important beneficiaries of such initiatives giving their disadvantaged position and their prominent role in cassava processing and marketing of gari.